Chemical disinfectants and antiseptics. Quantitative suspension test for the evaluation of bactericidal activity against Legionella of chemical disinfectants for aqueous systems. Test method and requirements (phase 2, step 1). (2nd November 2020) - British Standards Institution,
No abstract available